Advances in treatment and prevention of hepatitis B - Shah, Niraj James (World J Gastrointest Pharmacol Ther, 2021)
Chronic hepatitis B (CHB) continues to contribute to worldwide morbidity and mortality significantly. Scientists, clinicians, pharmaceutical companies, and health organizations have dedicated substantial Intellectual and monetary resources to finding a cure, increasing immunization rates, and reducing the global burden of CHB. National and international health-related organizations including the center for disease control, the national institute of health, the American Association for the study of liver disease (AASLD), The European association for the study of the Liver (EASL), The Asia Pacific association for the study of the Liver (APASL) and the world health organization release periodic recommendations for disease prevention and treatment. Our review of the most recent guidelines by EASL, AASLD, APASL, and Taiwan Association for the Study of the Liver revealed that an overwhelming majority of cited studies were published before 2018. We reviewed Hepatitis B-related literature published 2018 onwards to identify recent developments and current barriers that will likely direct future efforts towards eradicating hepatitis B. The breakthrough in our understanding of the hepatitis B virus life cycle and resulting drug development is encouraging with significant room for further progress. Data from high-risk populations, most vulnerable to the devastating effects of hepatitis B infection and reactivation remain sparse. Utilization of systems approach, optimization of experimental models, identification and validation of next-generation biomarkers, and precise modulation of the human immune response will be critical for future innovation. Within the foreseeable future, new treatments will likely complement conventional therapies rather than replace them. Most Importantly, pragmatic management of CHB related population health challenges must be prioritized to produce real-world results.